The (S)Pacific Effects of Sunday Morning Hockey: A Participant′s Observation - Turner, David (Culture, 1992)
This second commentary complements Dr. Tolvanen′s perspective by creating a metaphor of contemporary Canadian political issues in the guise of an analysis of a Sunday Morning Hockey league.